To Improve the Effectiveness of Investigations of the Crime of Morning Crime Clearance at Madiun City Police - Putra, Dihhan Laurent Ananda (Police Studies Review, 2024)
The increasing crime of theft has become a major problem that has an impact on security and order in society. Increasing criminal acts of theft can be disturbing social security situation in society. Strengthened by the low crime clearance rate of course It is a concern for the police to maximize their performance in resolving criminal cases criminal. This research was conducted with the aim of making the action investigation process more effective criminal theft to increase crime clearance at the Madiun City Police. The author uses a qualitative approach through interviews, observations and studies document. The type of research that the author carried out was by direct observation of the target study. The focus of the research is on the effectiveness of investigations carried out by the Police Criminal Investigation Unit Madiun City in handling criminal acts of theft so that it can increase the crime rate clearance. The results of the research show that there has been a spike in cases of criminal acts of theft at Madiun Police City in 2022 and the crime clearance rate for theft crimes has not been maximized in this period the last three years. Based on the results of the analysis carried out by the author, the process is less effective investigation is caused by a lack of information technology tools which are one of the means of evidence, the lack of public knowledge regarding theft crimes and the absence of an MOU between the parties police with network operator service providers related to data requests. Therefore, the author provides suggestions and input to the Madiun City Police Criminal Investigation Unit to make the process of investigating criminal acts of theft more effective, namely by adding technology CCTV technology at every point where there is a risk of crime and making an MOU between the parties investigator with the network operator service provider.